TINDAK TUTUR KOMISIF DAN EKSPRESIF DALAM DEBAT CAPRES-CAWAPRES PADA PILPRES 2019 - Febriani Khatimah Herfani; Ngusman Abdul Manaf (Jurnal Bahasa dan Sastra, 2020)
This study aims to: (1) formulate the types of commissive speech acts used by presidential and vice presidential candidates in the presidential and vice presidential debates at the 2019 presidential election, (3) formulate the types of expressive speech acts used by presidential and vice presidential candidates in the presidential and vice presidential debates at the 2019 presidential election, (2) formulating the speech strategy used by presidential and vice presidential candidates in the presidential and vice presidential debates at the 2019 presidential election. This type of research is a qualitative research with descriptive methods. The data source in this study is the speech of the 2019 presidential and vice presidential candidates downloaded via Youtube. Based on the results of data analysis, three findings were concluded. First, the types of commissive speech acts used by presidential and vice-presidential candidates in the presidential and vice presidential debates at the presidential election, namely (1) promising, (2) vowing, (3) offering, (4) swearing, and (5) intending. Second, the types of expressive speech acts that exist in the vice presidential debate in the 2019 presidential election are, (1) congratulate, (2) say thank you, (3) apologize, (4) praise, (5) criticize, (6) insinuate , and (7) complaining. Third, the speech strategy used in the vice presidential candidate debate in the 2019 presidential election, (1) speaking without further ado, (2) speaking with positive politeness politeness, (3) speaking with negative politeness pleasantries, and (4) speak vaguely.